Fish consumption in India: Patterns and trends - Panemangalore, Arun; Dubey, Sourabh; Bayan, Baban; Chadag, Vishnumurthy Mohan; Belton, Ben; Jena, Joykrushna; Mathew, Suseela; Murthy, Lakshmi; Karthikeyan, Muthusamy; Murthy, Chandra (WorldFish, 2024)
This study investigates the dynamics of fish consumption in India from 2005 to 2021, using comprehensive, nationally representative surveys conducted by the Government of India. It reveals significant growth in fish consumption in India, driven by population growth, increased wealth and shifting consumption patterns. The findings suggest potential for further growth and highlight regional disparities that could inform policy and intervention strategies.